Peningkatan Kapasitas dan Pengemasan Produksi Bagi Usaha Makanan Rumahan padat Karya - Ishak, Aulia; Napitupulu, Humala Lodewijk; Tarigan, Ukurta; Asfriyanti, Asfriyanti; M. Sari, Rahmi; Aguslina S, Fazidah (Jurnal Pengabdian Agro and Marine Industry, 2024)
The homemade snack food business is rapidly growing due to the high interest of the community in a variety of food options. Homemade food products are chosen because they are considered to have better quality and cleanliness. For example, sweet potatoes are processed into chips, and equipment such as sweet potato slicers and pots for frying sweet potatoes are crucial factors in determining the outcome of the chips. Initial observations with partners indicate difficulties in slicing and frying sweet potatoes due to limited equipment. Partners only have a double-edged knife for slicing sweet potatoes, resulting in unfulfilled customer orders. Emmi Snack Business faces challenges in meeting customer orders and requires innovation in attractive and secure packaging to ensure product quality.In this community service initiative, the main goal is to provide simple technological tools such as sweet potato slicers and fryers to increase production, as well as packaging equipment such as a vacuum sealer. This initiative also includes training on the use and maintenance of the equipment, as well as training on business management and simple bookkeeping. The results of this initiative will be published through scientific articles covering the service process and the achievements attained.